SUFISM AND VIRTUAL PIETY: A Narration of the Millennial Murshid in North Sumatra (JOURNAL OF INDONESIAN ISLAM, 2022)
The millennial murshid comprises young tariqah leaders, who are well-versed in the latest information technology. Sufism identity has changed under the millennial murshid due to the development of information technology and their participation in social media which tries to revive the doctrine and ritual in the changing global reality. This condition has fostered Sufistic activism in a new direction from a â€œquiet roadâ€ to a â€œpublic roadâ€ in cyberspace. This article has explored the intersection between Sufism and social media based on the narration of the millennial murshid of Tariqa Naqshabandiyya-Khalidiya Serambi Babussalam. The findings illustrate that the phenomenon of virtual Sufism that has emerged from the intersection between Sufism and social media has given birth to a new expression of piety called as virtual piety. It is a simplification of piety from the original form of Sufistic tradition that emphasizes symbolic-esoteric aspects and is likely as opposed to individual piety. Additionally, the millennial murshid has successfully used social media, particularly Facebook, to reach out to the online community and gain followers.